A Systematic Review of Mobile-Based Assessment Acceptance Studies from 2009 To 2019 - Alrfooh, Ali; Lakulu, Muhammad Modi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Despite many studies being conducted on mobile learning acceptance, few investigate mobile-based assessment acceptance. The objectives of this research are to provide valuable insights into current research on mobile-based assessment literature, and to identify the main gaps in the mobile-based assessment acceptance literature. Therefore, the present study systematically reviews 48 previous studies and eight articles related to mobile-based assessment acceptance to provide a comprehensive analysis of the articles published from 2009 to 2019. Findings indicate that majority of mobile-based assessment studies focused on evaluating the effectiveness and performance of mobile-based assessment system and conducted at the secondary school level. In addition, this study identified several gaps. Further research is needed to study the acceptance problem of a mobile-based assessment system. More investigation is required to predict which external factors that can enhance the acceptance and use of mobile-based assessment among students. The findings of this review study provide a valuable reference for researchers about the current trend of mobile-based assessment research as well as the research gaps that should be covered in future studies.